The Impact Of Follow-Up On Audit Recommendations On The Audit Opinion Of Regional Financial Statements In Central Sulawesi (2019-2023) - Lamading, Maharani; Ridwan; Din, Muhammad; Masruddin (Balance : Jurnal Akuntansi dan Manajemen, 2025)
This study aims to analyze the influence of the Follow-up of Audit Recommendations (TRLHP) on the Opinion on the Regency/City Regional Government Financial Statements (LKPD) in Central Sulawesi Province. Using a quantitative approach, the secondary data used came from the Central Sulawesi Provincial Representative Financial Audit Agency (BPK) regarding the follow-up of recommendations in the 2019-2023 period. Data analysis was carried out using the PLS SEM method through WarpPLS 8.0. The results of the study showed that the Follow-up of the Audit Recommendations had a positive and significant effect on the opinion of the Regional Government Financial Statements, with a path coefficient of β = 0.65 and a significance of P < 0.01. An R² value of 0.43 indicates that the Follow-up variable of the Audit Results Recommendation explains 43% of the variability of the Opinion. These findings indicate that the follow-up of recommendations has the potential to improve the quality of the opinion of the Financial Statements of Regency/City Regional Governments in Central Sulawesi Province. Although this variable explains 43% of the variation in opinion, there are still other factors that contribute. This study suggests a qualitative approach for further studies to explore the relationship between audit and compliance and the impact of the surveillance system on corruption prevention.